Simbolisasi dan Makna Kekerasan Seksual dalam Film Tuhan, Izinkan Aku Berdosa: Perspektif Clifford Geertz - juanda, Dilla Paramita; Juanda; Bungatang (Universitas Insan Budi Utomo, 2025)
This research aims to describe the symbolization and meaning of sexual violence in the film God, Allow Me to Sin. This type of research uses a qualitative descriptive method approach. The data source comes from the movie God, Allow Me to Sin, which aired in theaters on May 22, 2024, and was directed by Hanum Bramantyo. The techniques used in collecting data are observation and notes that are in accordance with the focus of study. The data was analyzed using Clifford Geertz’s scalpel. Based on the research results, there are two symbols, namely visual symbols and non-visual symbols. Non-visual symbols consist of symbols, object symbols, and place symbols. In comparison, non-visual symbols consist of action symbols. In contrast, non-visual symbols consist of action symbols and dialogue text symbols. The benefits of this research are that sexual violence is not only carried out in the form of physical sexual violence is not only carried out in the form of physical sexual violence but can also occur verbally and visually so that it can increase critical awareness of the representation of sexual violence in the media, especially films and women are expected to have more critical awareness and empowerment to reject and resist domination that harms them.